Microparticles from apoptotic vascular smooth muscle cells induce endothelial dysfunction, a phenomenon prevented by β3-integrin antagonists - Essayagh, Sanah; Brisset, Anne-Cecile; Terrisse, Anne-Dominique; Dupouy, Dominique; Tellier, Lise; Navarro, Chantal; Arnal, Jean-François; Siè, Piérre (Thrombosis and Haemostasis, 2005)
Fragile atherosclerotic plaques are rich in apoptotic smooth muscle cells (SMCs) and macrophages, generating microparticules (MPs) which accumulate locally and may be released in blood in case of mechanical or spontaneous plaque disruption. Besides being highly procoagulant, this material may interact with downstream endothelium. Using a model of mouse aorta vaso-reactivity, we have investigated the effects of apoptotic MPs preparedin vitro from Fas-ligand sensitive SMCs. Short-term preincubation of aorta rings with the MPs dose-dependently reduced the vasodilatory response to acetylcholine dependent on the endothelium. This effect was prevented by the addition of abxicimab or eptifibatide, indicating a role for a β3 integrin in thisprocess. We further investigated its mechanism using cultured endothelial cells. The MPs were found to bind to the cells and to inhibit the production and the release of nitric oxide (NO) in response to bradykinin. This phenomenom was redox sensitive, independent of the generation of activated coagulation proteases, and was abrogated when the MPs were pretreated by trypsin. The metabolic effects of MPs were prevented by the addition of eptifibatide. Taken together, these results suggest a potential, platelet-independent, mechanism for the improvement of microvascular perfusion observed with β3-integrin antagonists.
Keywords: Microparticles; nitric oxide; endothelium; vasorelaxation; β3-integrin antagonists